THE TEACHERS`PERCEPTIONS OF TEACHING PROGRAMMING AT EIGHT- YEAR GRAMMAR SCHOOLS - Milan, KLEMENT; LAVRINČÍK, Jan (Trends in education, 2013)
Teaching programming at secondary schools, focused on the acquisition of general knowledge by the students, is a relatively new and unexplored area. To enable a creation, design, and implementation of the syllabus pertaining to the teaching of the basics of programming, it is essential to continuously identify and evaluate the views and opinions of individual participants in this training process. Subsequently, based on these analyzes, it is possible not only to determine the suitability of this particular subject for teaching as a whole, but also the benefits and possible risks related to the latter.For these reasons, a joint project of six eight-year grammar schools in Olomouc Region and the Department of Technical and Information Education of PdF UP Olomouc was implemented. Its aim was the insertion of the subject "Introduction to Programming" to the curriculum, and the evaluation of its benefits according to teachers who taught it. This assessment took the form of a survey research, the selected partial results of which shall be submitted by this article.
Keywords: programming; teaching programming; Visual Basic; survey research